Hubungan Layanan Keperawatan Dengan Tingkat Kepuasan Pasien Rawat Inap di Rumah Sakit Murni Teguh Medan - Nelvin Novitasari Mendrofa; Rustianna Tumanggor (PT. Hasba Edukasi Mandiri, 2025)
Background: Nursing services are a series of actions provided by trained nursing staff to meet patient health needs. This service aims to maintain, restore and improve the patient's health and quality of life through comprehensive, holistic and patient-centered nursing care. The quality of nursing services is one of the key factors that influences the level of patient satisfaction during hospital treatment. Method: This research used a pre-experimental design, with a cross sectional design. Population and sample: Sampling used the Accidental sampling method with the Slovin calculation model. The total research sample was 74 respondents from a population of 280 inpatients. The research instruments used were the nursing service questionnaire and patient satisfaction questionnaire. Data analysis: Using the Chi Square test. Results: The results of the study show that there is a relationship between nursing services and the level of satisfaction of inpatients at Murni Teguh Hospital in Medan. The Chi Square Statistical Test shows the p value = 0.01 < 0.05. Conclusion: There is a relationship between nursing services and the level of satisfaction of inpatients at Murni Teguh Hospital in Medan